DISRUPTION OF MEDIA IN POLITICAL SPACES AND POST-TRUTH ERA - Dalimunthe, Syairal Fahmy (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
The dynamics of the internet to connect and transmit information make rapid changes to communication globally. The presence of the internet is part of a process of cultural change. These changes occur because of the disruption of internet. In the political process, people often use new media to organize campaign actions, help the  elections in the open way, and provide greater space for independent opinion and expression in cyber space.  Social media such as Facebook, Twitter, Instagram, Blogs, YouTube, WhatsApp and others become a fact of disruption, replaced the mainstream media that is commonly used in political campaigns. The emergence of political buzzers with followers often changes the format of the campaign to be more open, critical and actual. Buzzers who work independently without official institutions cause them to become producers of information based on their own opinions and are free to side with certain parties or political figures. Openness of digital information in the post-truth era has caused people to be flooded with information. The problem that arises later in the community is not how to get the news, but rather the lack of ability to digest information properly. Post-truth makes the position of opinion above facts, lies and hate speech become  commodities in politics industries in the digital space.